Músicos célebres - Brower, Harriette
Contiene: Palestrina, Juan Sebastián Bach, Handell, C. Willibald Gluck, Hadyn, Mozart, Beethoven, Weber, Schubert, Mendelssohn, Shumann, Chopin, Berlioz, Liszt, Verdi, Wagner, Franck, Brahms, Grieg, Macdowell, Tshaikowsky, C. Aquiles Debussy.